Effects of elutriates from contaminated coastal sediments on different life cycle phases of planktonic diatoms. (March 2020) - Pelusi, A.; Rotolo, F.; Gallo, A.; Ferrante, M.I.; Montresor, M.
Abstract: We assessed the effects of elutriates from sediments collected at three stations in the polluted Bay of Bagnoli-Coroglio along the Campania coast (Tyrrhenian Sea, Italy) using three planktonic diatoms regularly occurring in the area, Pseudo-nitzschia multistriata, P. arenysensis and Chaetoceros socialis . Specifically, we tested the production of sexual stages in the heterothallic Pseudo-nitzschia species with the hypothesis that pollutants could impair sexual reproduction. We also tested the seeding capacity of spores of C. socialis after up to six months of storage in elutriates, assuming that pollutants could affect the capability of resting stages to germinate. Elutriate from station 56, with the highest concentrations of pollutants, impaired growth, sexual reproduction and spore germination. Elutriates from stations 25 and 84 caused moderate enhancement of growth and sexual reproduction in Pseudo-nitzschia as compared with control conditions, and also had intermediate effect on spore seeding capacity. Highlights: The toxicity of marine sediments was tested on specific life cycle phases of marine diatoms. Elutriates with high concentration of PAHs impaired cell growth and sexual reproduction in Pseudo-nitzschia . The seeding capacity of resting spores of Chaetoceros socialis was negatively affected. Testing life cycle features improves our understanding of the potential impact of pollutants on phytoplankton communities.